Pretreatment with Mangafodipir Improves Liver Graft Tolerance to Ischemia/Reperfusion Injury in Rat - Ben Mosbah, Ismail; Mouchel, Yann; Pajaud, Julie; Ribault, Catherine; Lucas, Catherine; Laurent, Alexis; Boudjema, Karim; Morel, Fabrice; Corlu, Anne; Compagnon, Philippe (PLOS ONE, 2012)
Ischemia/reperfusion injury occurring during liver transplantation is mainly due to the generation of reactive oxygen species (ROS) upon revascularization. Thus, delivery of antioxidant enzymes might reduce the deleterious effects of ROS and improve liver graft initial function. Mangafodipir trisodium (MnDPDP), a contrast agent currently used in magnetic resonance imaging of the liver, has been shown to be endowed with powerful antioxidant properties. We hypothesized that MnDPDP could have a protective effect against liver ischemia reperfusion injury when administrated to the donor prior to harvesting. Livers from Sprague Dawley rats pretreated or not with MnDPDP were harvested and subsequently preserved for 24 h in Celsior® solution at 4°C. Organs were then perfused ex vivo for 120 min at 37°C with Krebs Henseleit solution. In MnDPDP (5 µmol/kg) group, we observed that ATP content was significantly higher at the end of the cold preservation period relative to untreated group. After reperfusion, livers from MnDPDP-treated rats showed better tissue integrity, less hepatocellular and endothelial cell injury. This was accompanied by larger amounts of bile production and higher ATP recovery as compared to untreated livers. The protective effect of MnDPDP was associated with a significant decrease of lipid peroxidation, mitochondrial damage, and apoptosis. Interestingly, MnDPDP-pretreated livers exhibited activation of Nfr2 and HIF-1α pathways resulting in a higher catalase and HO-1 activities. MnDPDP also increased total nitric oxide (NO) production which derived from higher expression of constitutive NO synthase and lower expression of inducible NO synthase. In conclusion, our results show that donor pretreatment with MnDPDP protects the rat liver graft from cold ischemia/reperfusion injury and demonstrate for the first time the potential interest of this molecule in the field of organ preservation. Since MnDPDP is safely used in liver imaging, this preservation strategy holds great promise for translation to clinical liver transplantation.